Effects of using a finned cylindrical cooler in the nano-enhanced cooling channel on the exergetic performance of a PV/TEG-coupled system - Selimefendigil, Fatih; Okulu, Damla; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2024)
In this study, three different nano-enhanced channel models were integrated into the 3D photovoltaic (PV)/thermoelectric generator (TEG) system and the effect of the channel models on the PV/TEG system performance was examined. The flat rectangular channel, Model 1 while the cylindrical and fin-reinforced cylindrical object accommodated in the flat rectangular channel are defined as Model 2 and Model 3, respectively. A comparison of water and ternary nanofluid with various nanoparticle (solid particle volume fraction between 0.01 and 0.03) loading was performed in each channel model. In addition, impacts of cooling fluids at different inlet temperatures (Tg between 25 degrees C and 12.5 degrees C) were considered in the simulations. Among different cooling channels, lowest PV cell temperature and the highest PV output power were obtained in Model 3. The highest PV power (0.51 W) was obtained with Model 3 with ternary nanofluid (%3 volume fraction) at Tg = 12.5 degrees C. This value is is 3.66% and 4.03% higher than Model 2 and Model 1, respectively. Under the same conditions, TEG output power reached its highest value with Model 2 and it was followed by Model 1 and Model 3, respectively. With the reinforcement of fins to the cylindrical object, an improvement in thermal performance was achieved, but a decrease in total output power was observed.
Keywords: TEG/PV; cooling channels; finned cylinder; computational fluid dynamics; exergy; sustainability